Radio Eska Łódź, czyli lokalne radio sieciowe - Szews, Przemysław (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2015)
The article discusses aspects of network-based local radio using the example of Radio Eska Lodz. The author responds to questions about whether a commercial network radio station can fulfill the functions of local radio and on what this locality is actually based. In this respect, Radio Eska Lodz is characterized as part of the most popular commercial radio network in Poland. The introduction focuses on the process of transformation that local radio stations are undergoing, along with its genesis. The author then considers whether the radio station described is fulfilling the goals of local radio and how it looks in comparison to other cities.